Integrating Y, Star, and Interpersonal Communication Patterns to Enhance the Tahfidzul Qur’an Program at Pesantren Ar-Rahmah - Salman, Muhammad (Pesantren and Community Development Studies - Islamic Institute of Syarifuddin, Indonesia., 2024)
This article explores the role of Pesantren Tahfidzul Qur’an Ar-Rahmah in nurturing a generation of Muslims who not only memorise the Qur’an but also comprehend and embody its teachings in daily life. While producing students who can memorise the Qur’an is relatively straightforward, cultivating high-quality memorizers through effective methods is significantly more critical. This study adopts a qualitative descriptive approach with participatory observation as its primary data collection method. The findings indicate that the communication patterns employed by the pesantren are based on the Y and Star communication models, which facilitate two-way interactions among caretakers, teachers, and students. Interpersonal communication emerges as a central element in the intensive mentoring process led by the asatidz and musyrif, who serve not only as educators but also as spiritual guides and motivational figures. The study also identifies several internal inhibiting factors that impact the effectiveness of the Qur’anic memorisation programme, such as lack of motivation, laziness, and tendencies among students to skip memorisation sessions. It concludes that the success of the Tahfidzul Qur’an programme is closely tied to the effectiveness of communication strategies and the emotional closeness cultivated through consistent and structured interpersonal engagement.